2012
DOI: 10.30972/vet.2311798
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to peroxidation and fatty acid composition of fresh boar semen obtained from different hog farms

Abstract: <p>Objectives of this study were to determine the fatty acid composition and to analyze the sensitivity to lipid peroxidation of different boar fresh semen samples from two herds, H1 and H2. Lipid peroxidation was evaluated using chemilu­minescence (cpm/mg of protein) and fatty acid profile by means of gas chromatography. The saturated fatty acid content found in the analyzed spermatozoa was approximately 43% in H1 and 33% in H2, whereas the total unsaturated fatty acid content was 47% in H1 and 59% in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Regarding the effects of ChA on viability after 72 hr of storage, it is well known that excessive intracellular ROS levels induce cell damage often resulting in cell death (Marmunti et al., ; Waterhouse et al., ). In this study, the anti‐ROS effect of ChA was suggested by the improvement in the sperm viability and motility and the percentage of structurally intact acrosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the effects of ChA on viability after 72 hr of storage, it is well known that excessive intracellular ROS levels induce cell damage often resulting in cell death (Marmunti et al., ; Waterhouse et al., ). In this study, the anti‐ROS effect of ChA was suggested by the improvement in the sperm viability and motility and the percentage of structurally intact acrosomes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important causes of reduced semen quality during storage time is the presence of reactive oxygen species (ROS), which in turn cause oxidative damage in sperm cell membranes (Waterhouse et al., ). The presence of ROS is almost always related to the alteration of permeability and cell membrane function, apoptotic‐like modifications in the cells (Marmunti, Gutiérrez, Gavazza, Williams, & Palacios, ), reduction in sperm motility and fertility capacity of the semen (Martin‐Hidalgo et al., ). To reduce the damage caused by ROS, antioxidant substances are commonly added to the semen dilution media, ensuring better quality of the cooled semen (Breininger, Beorlegui, O'Flaherty, & Beconi, ; Martin‐Hidalgo et al., ; Mendez et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive ROS can damage the sperm by causing the lipid peroxidation (LPO) and DNA damage. LPO also reduces the level of PUFA (Marmunti et al, 2012). Egg yolk (15% to 20%) has been used for over 40 years as a standard membrane-modifying agent that is added to traditional semen cryopreservation extender (Phillips and Lardy, 1940;Visser and Salamon, 1974).…”
Section: Replacing Of Egg Yolk With Lecithin In Boar Semen Cryopreser...mentioning
confidence: 99%